ARABIC TRANSLATION TECHNIQUES OF COVID-19 TERMS IN THE DAILY ARABIC NEWSPAPER OF INDONESIAALYOUM.COM - Adrian Surya Da Cunha; Yoyo Yoyo; Abdul Razif Zaini (STIQ Amuntai, 2022)
As an international language, Arabic develops continuously. Arabic development in various fields was triggered by the development of science, technology, and arts. This development continues to be carried out by adapting and translating new terms, forming new terms, absorbing them from the source language, and harmonizing with Arabic rules. This research is qualitative with a library research approach and uses the descriptive analysis method. This study aims to analyze the technical translation of the covid-19 terms in Arabic on the news page